Boundary value problem with integral conditions for a linear third-order equation. Issue 11 (2nd December 2003) - Denche, M.; Memou, A.
Abstract : We prove the existence and uniqueness of a strong solution for a linear third-order equation with integral boundary conditions. The proof uses energy inequalities and the density of the range of the generated operator.